Clinical experiences with robotic computed tomography-guided interventions: A comparison with manual technique - Ashwin Kumar A; Sivakumar Kannappan; Geetha G (Asian Journal of Medical Sciences)
Background: Image-guided biopsies have become standard practice; however, challenges such as multiple punctures and re-attempts can complicate procedures. The introduction of robotic guidance systems, such as MAXIO offers a potential solution for improving planning and navigation. This study evaluated the efficacy of the MAXIO needle-guiding robotic device in computed tomography (CT)-guided interventions compared with conventional manual techniques.